High Child-Pugh and CRUB65 scores predict mortality of decompensated cirrhosis patients with COVID-19: A 23-center, retrospective study. Issue 1 (31st December 2021) - Xiao, Yong; Wu, Dongwen; Shi, Xiao; Liu, Shuzhong; Hu, Xudong; Zhou, Chenliang; Tian, Xia; Liu, Huimin; Long, Hui; Li, Zhihong; Wang, Ji; Tan, Tao; et al.
ABSTRACT: Background : COVID-19 has rapidly become a major health emergency worldwide. The characteristic, outcome, and risk factor of COVID-19 in patients with decompensated cirrhosis remain unclear. Methods : Medical records were collected from 23 Chinese hospitals. Patients with decompensated cirrhosis and age- and sex-matched non-liver disease patients were enrolled with 1:4 ratio using stratified sampling. Results : There were more comorbidities with higher Chalson Complication Index (p < 0.001), higher proportion of patients having gastrointestinal bleeding, jaundice, ascites, and diarrhea among those patients (p < 0.05) and in decompensated cirrhosis patients. Mortality (p < 0.05) and the proportion of severe ill (p < 0.001) were significantly high among those patients. Patients in severe ill subgroup had higher mortality (p < 0.001), MELD, and CRUB65 score but lower lymphocytes count. Besides, this subgroup had larger proportion of patients with abnormal (PT), activated partial thromboplatin time (APTT), D-Dimer, alanine aminotransferase (ALT), aspartate aminotransferase (AST), total bilirubin (TBL) and Creatinine (Cr) (p < 0.05). Multivariate logistic regression for severity shown that MELD and CRUB65 score reached significance. Higher Child-Pugh and CRUB65 scores were found among non-survival cases and multivariate logistic regression further inferred risk factors for adverse outcome. Receiver Operating Characteristic (ROC) curves also provided remarkable demonstrations for the predictive ability of Child-Pugh and CRUB65 scores. Conclusions : COVID-19 patients with cirrhosis had larger proportion of more severely disease and higher mortality. MELD and CRUB65 score at hospital admission may predict COVID-19 severity while Child-Pugh and CRUB65 score were highly associated with non-survival among those patients.